Bioprosthetic Valve Remodeling of Trifecta Surgical Valves to Facilitate Valve-in-Valve TAVR. Issue 2 (3rd March 2020) - Saxon, John T.; Allen, Keith B.; Cohen, David J.; Hart, Anthony; Dvir, Danny; Chhatriwalla, Adnan K.
ABSTRACT: Background: Valve-in-valve transcatheter aortic valve replacement (VIV TAVR) is an effective treatment for high-risk patients with failed surgical bioprosthetic valves, but may be complicated by patient-prosthesis mismatch (PPM). We describe a novel technique – bioprosthetic valve remodeling (BVR) – to distort the frame of Trifecta surgical valves with a high-pressure balloon inflation, allowing for improved expansion and hemodynamics of the transcatheter heart valve (THV). Methods: We performed bench testing of BVR by deploying Portico THVs (Abbott, Minneapolis, MN, USA) inside Trifecta GT valves both at baseline and following BVR. Fluoroscopic and video imaging was performed to assess Trifecta frame distortion, THV expansion, and leaflet motion. Hydrodynamic testing was performed to determine transvalvular gradient under baseline conditions and following BVR. We performed 6 clinical cases of VIV TAVR with Evolut R THVs (Medtronic, Minneapolis, MN), followed by BVR. Hemodynamic measurements and calculation of the effective orifice area (EOA) were performed at baseline, immediately after implantation of the THV, and after BVR. Results: BVR resulted in an increase in the post-to-post diameter in Trifecta valves, and a lower transvalvular gradient after THV implantation. VIV TAVR and BVR was successful in all cases, with no major short-term complications. The mean baseline transvalvular gradient was 47.5 ± 14.4 mmHg, which was reduced to 21.0 ± 6.2 mmHg after THV implantation, and further reduced to 11.7 ± 4.1 mmHg following BVR. Gradients were stable at 1 month follow up. Conclusion: BVR distorts the frame of Trifecta valves, improving THV expansion and procedural hemodynamics of VIV TAVR.